Beyond utopia : Japanese Metabolism architecture and the birth of mythopia - Nyilas, Agnes, 1973- (Routledge, Taylor & Francis Group, 2018)
Megastructure proposals by the Japanese Metabolism group are commonly identified with the concept of utopia. Beyond this partial understanding, the author suggests that rather than being merely utopian, the Megastructure of Metabolism represents a uniquely amalgam genre: the myth camouflaged as utopia. Although its Megastructure seemingly describes a desirable future condition as utopia does, it also comprises certain cultural images rooted in the collective (un)conscious of Japanese people, in accordance with the general interpretation of myth. The primary narrative of the book thus follows the gradual unfolding of the myth-like characteristics of its Megastructure. Myth is dealt here as an interdisciplinary subject in line with contemporary myth theories. After expounding the mechanism underlying the growing demand for a new myth in architecture (the origin of the myth), Part I discovers the formal characteristics of the Megastructure of Metabolism to give a hint of the real intention behind it. Based on this, Part II is a reexamination of their design methods, which aims to clarify the function of the myth and to suggest the meaning behind it. Finally, Part III deals with the subject matter of the myth by disclosing the meaning unfolding in the story, and suggests a new reading of Metabolism's urban theory: as an attempt to reconsider the traditional Japanese space concept.